A greeting of the spirit : selected poetry of John Keats with commentaries - Keats, John, 1795-1821; Wolfson, Susan J., 1948-; Keats, John, 1795-1821. (Cambridge, Massachusetts The Belknap Press of Harvard University Press, 2022)
"A renowned Keats scholar illuminates the poet's extraordinary career, in a new edition featuring eighty-five verse selections with commentary. A Greeting of the Spirit greets everyone at every level of expertise who is interested in this extraordinary poetry of John Keats, interested in extraordinary imagination, interested in reading with care: adventurous undergraduates, graduate students, professional peers, and with its lucidity of style and access, anyone open to a spirited engagement with remarkable, phenomenal poetry"--
Frontmatter -- Contents -- Author's note on text and style -- Abbreviations -- Illustrations -- Introduction -- Sonnet Ventures: April 1814-April 1817 -- Poems and a "Long Poem" March 1817-March 1818 -- Training, Retraining, "New Romance" December 1817-May 1818 -- To the North, to the North: Summer 1818 -- Wide Venturing: Fall 1818-April 1819 -- Garlands of their Own: Spring-Summer 1819 -- All I Live For: Last Poems, August 1819-Winter 1820 -- Ending, Unending -- Postscript -- Time-Lines -- Works Cited -- Acknowledgments -- Index
Includes bibliographical references and index
Description based on print version record
JSTOR
Keywords: Keats, John, -- 1795-1821.; Keats, John, -- 1795-1821; POETRY / European / English, Irish, Scottish, Welsh; Poetry; poetry; Poetry; Poetry; Poésie.